“What If I Aint Ate in 2 Days, Why the Hell Would I Want You to Poke Into My Arm”: A Critical Cultural Analysis of Testing Makes Us Stronger - Hawkins, Deion Scott (Frontiers in Communication, 2020)
Despite medical advancements, Black gay, bisexual and other men who have sex with men (BMSM) are the group most disproportionately impacted by HIV in the United States. Recent figures estimate one in two Black MSM will be diagnosed with HIV in their lifetime. From 2011 to 2015, the Center for Disease Control ran Testing Makes Us Stronger, a health communication campaign designed to increase rates of HIV testing in the Black MSM community. Past studies document the campaign’s visibility, but fail to explain the continuous rise of HIV transmissions within the Black MSM community. Previous research on Testing Makes Us Stronger analyzes exposure to the campaign, but fails to capture the experiences and opinions of its target audience. Using the Culture-Centered Approach, this study conducted 20 semi-structured phone interviews to unveil how culture and systemic inequities influence rates of HIV transmission in the Black MSM community. Thematic analysis found three key themes: (1) trans invisibility, (2) call for holistic approaches and (3) importance of local organizations. Findings from the study suggest HIV campaigns would benefit from working in tandem with other organizations designed to combat systemic inequalities. Keywords: HIV, Black MSM, testing, campaign, critical health